War of the Whales: Climate Change, Weather and Arctic Conflict in the Early Seventeenth Century. (1st November 2020) - Degroot, Dagomar
Beginning in 1580, average annual temperatures across the Arctic cooled amid the regional onset of the 'Grindelwald Fluctuation', a particularly cold but volatile period in the Little Ice Age. By contributing to socioeconomic trends that raised the cost of vegetable oils, climatic cooling encouraged European merchants to establish rival whaling operations around the frigid archipelago of Svalbard, roughly halfway between Norway and the North Pole. From 1611 until 1619, European whalers depended on temporary encampments set up along the shores of bays in the islands of Svalbard, and eventually the nearby island of Jan Mayen. When regional sea ice registered the climatic trends of the Grindelwald Fluctuation by besetting these bays, whalers from different European nations and companies coped by cooperating with one another. Yet when the volatility of the Grindelwald Fluctuation in the already variable climate of Svalbard and Jan Mayen drew ice away from the bays, violence often broke out between rival whalers and their escorting warships. Shifting environmental circumstances therefore played a previously ignored role in inciting and mitigating violence in the first decade of the Spitsbergen whaling industry. These relationships can offer new perspectives on the future of geopolitical competition in a warming Arctic.